Development and Evaluation of Eco-friendly Biopesticides Against Aphids and Pod borer of Food Legumes in Morocco in 2024 - Boulamtat, Rachid; Kemal, Seid Ahmed (International Center for Agricultural Research in the Dry Areas, 2024)
Due to weather variability, chickpea pod borer on chickpea and green pea aphids are economically important insect pests. Besides their economic damage, aphids play a role as virus vectors on food legumes. This study aimed to validate eco-friendly entomopathogenic fungi and essential oils (EOs) formulated with Chitosan+Tween against aphid under controlled and field conditions. Two entomopathogenic fungi (Beauveria bassiana- strain- SGSK and Verticillium lecanii- Strain-SPT-2-271) were tested under controlled and field conditions. The formulated EOs and entomopathogenic fungi were effective against green pea aphids on lentil and chickpea pod borer, respectively. Entomopathogenic fungi and formulated EOs can be integrated in the management of pod borers and aphids as eco-friendly alternative pest management options in Morocco. The ecofriendly biopesticides will be demonstrated on large plots under farmer condition in 2024/25 cropping season.